"Same-patient processing" for multiple cardiac SPECT studies. 2. Improving quantification repeatability. - Germano, Guido; Kavanagh, Paul; Ruddy, Terrence; Wells, R.; Xu, Yuan; Berman, Daniel; Slomka, Piotr; Kavanagh, Paul B; Ruddy, Terrence D; Wells, R Glenn; Berman, Daniel S; Slomka, Piotr J (Journal of Nuclear Cardiology, 2016)
Objectives: This paper investigates the ability of grouped quantification (an expression of the same-patient processing approach, or SPP) to improve repeatability of measurements in patients with multiple SPECT studies, and evaluates its performance compared to standard quantification in a population of 100 patients undergoing rest, stress, gated rest, and gated stress SPECT MPI. All acquisitions were performed twice, back-to-back, for a total of 800 image datasets (8 per patient).Methods: Each dataset was automatically processed (a) independently, using standard quantitative software, and (b) as a group, together with the other 7 datasets belonging to the same patient, using an SPP-modified version of the software that registered the images to one another using a downhill simplex algorithm for the search of optimal translation, rotation, and scaling parameters.Results: Overall, grouped quantification resulted in significantly lower differences between repeated measurements of stress ungated volumes (1.40 ± 2.76 mL vs 3.33 ± 5.06 mL, P < .05), end-diastolic volumes (1.78 ± 2.78 vs 3.49 ± 5.35 mL, P < .05), end-systolic volumes (1.17 ± 1.96 vs 2.44 ± 3.35 mL, P < .05), and LVEFs (-0.45 ± 2.29% vs -1.16 ± 3.30%, P < .05). Additionally, grouped quantification produced better repeatability (lower repeatability coefficients) for stress and rest ungated volumes (5.4 vs 9.9 and 5.2 vs 13.1, respectively), stress TPD (2.6 vs 3.6), stress and rest end-diastolic volumes (5.5 vs 10.5 and 7.2 vs 14.7, respectively), stress and rest end-systolic volumes (3.8 vs 6.6 and 5.3 vs 10.3, respectively), stress and rest LVEFs (4.5 vs 6.5 and 4.7 vs 8.2, respectively), and rest total motion deficit (5.6 vs 9.6).Conclusion: It is possible to improve the repeatability of quantitative measurements of parameters of myocardial perfusion and function derived from SPECT MPI studies of a same patient by group processing of image datasets belonging to that patient. This application of the same-patient processing approach is an extension of the "paired processing" technique already described by our group, and can be performed in automated fashion through incorporation in the quantitative algorithm.